Educational Technology Innovation: AI-Integrated Learning System Design in AILS-Based Education - Soelistiono, Soegianto; Wahidin (Global Writing Academica Researching and Publishing, 2023)
Information and Communication Technology (ICT) has seamlessly integrated itself into modern society, revolutionizing education through its innovations. One prominent innovation is the Artificial Intelligence (AI)-based learning system, promising an elevated quality of education. The AI-based learning system harnesses machine learning to tailor approaches for each student, monitoring their progress and providing pertinent feedback. A noteworthy example is the Intelligent Adaptive Learning System (AILS), which amalgamates Natural Language Processing (NLP) technology and 3D animation with the Google Search Engine. AILS aids comprehension via tablet devices, with teachers concurrently assuming a supportive role. AILS empowers students to autonomously acquire knowledge, accessing information through NLP and the Google Search Engine. The visualization of teachers through 3D animations enhances interactivity. Through AILS, students can learn from home or in-class, guided and mentored by teachers. AILS efficiently processes data, monitors progress, offers feedback, and identifies student needs. Teachers continue to facilitate profound learning and critical thinking skills. AILS fosters self-directed learning and lifelong skills. Furthermore, AILS augments the quality of the educational framework, integrating AI technology to realize student self-directedness in the Society 5.0 era.